Site selection and dynamic modelling of Manila clam, Ruditapes philippinarum, in the Tagus Estuary - Serra, João Guilherme Valente Mendes (2017)
This thesis assesses the viability of shellfish aquaculture in the Tagus Estuary of the species Manila clam (Ruditapes philippinarum), by means of a GIS-based site selection and the application of a dynamic modelling software at farm-scale, in order to evaluate the potential production, environmental effects, and economic feasibility. The site selection for shellfish aquaculture is based on the application of a Multi-Criteria Evaluation in a GIS software. Both are useful tools for site selection, as when combined they help decision-makers to identify the existing spatial constraints and take into consideration key variables, such as (i) the external environmental conditions that regulate shellfish growth, (ii) existing infrastructures and socioeconomic variables that are relevant for production, and (iii) contaminated areas that may reduce the shellfish quality as a food product. The dynamic modelling software used, FARM (Farm Aquaculture Resource Management), was applied in accordance with the best areas identified as being suitable for shellfish aquaculture, where the production and profit of two different locations are estimated and compared at a farm-scale level, and further extrapolated to larger areas.